Africa's Best and Worst Presidents : How Neocolonialism and Imperialism Maintained Venal Rules in Africa. - Mhango, Nkuzi (Langaa RPCIG, 2016)
Africa's Best and Worst Presidents seeks to deconstruct the current superstructure that colonialism created and maintains. It chastises and challenges Africans, academics in the main, to revisit and write a true history of Africa. Written by Africans themselves, such rewritten histories should aim to counter the counterfeit narratives which have proliferated, poisoned and diminished African sense of self and self-confidence. The history centred on African perspectives and experiences should go a long way in our quest to truly unfetter Africa from dependency, desolations and mismanagement. This book calls upon all Africans to stand up fearlessly and tirelessly to take on decadent and despotic regimes that have always held Africa at ransom as they get lessons from the best managers of state affairs on whose feats they must expand. The option to critique, cross-examine and dissect past African presidents and their excesses is aimed at giving the young and frustrated generations of Africans the intellectual resources they need to arm themselves in resolve and pursuit of Africa's emancipation.